An assessment of factors associated with neurocognitive decline in people living with HIV. (January 2022) - Naveed, Zaeema; Fox, Howard S; Wichman, Christopher S; May, Pamela; Arcari, Christine M; Meza, Jane; Baccaglini, Lorena
Despite the widespread use of combination antiretroviral therapy (cART), HIV-associated neurocognitive impairment (NCI) remains a health concern. However, limited research has been done to identify factors associated with neurocognitive decline. We assessed risk factors associated with neurocognitive decline in people living with HIV using a definition of decline that is statistically easy to adopt, is based on a commonly used neuropsychological cut-off and may be clinically relevant. Cox proportional hazards modeling was performed using the CNS HIV Antiretroviral Therapy Effects Research (CHARTER) study database. 581 participants were followed for up to 12 years. Neurocognitive decline was defined as the first observed drop in global T-scores of at least 2.67. Lifetime methamphetamine use had the strongest association with neurocognitive decline (adjusted Hazard Ratio; aHR = 1.48; 95% CI = 0.92–2.39) followed by no current antiretroviral medication use (aHR = 1.32; 95% CI = 0.91–1.92). Other risk factors included Hispanic ethnicity, lifetime history of major depressive disorder, lifetime cannabis use, hepatitis-C infection, and difficulty eating, dressing, bathing, or using the toilet. Results indicate that consistent use of ART may be of high significance to preserving neurocognition. Furthermore, Hispanic patients, those with a history of depression and substance use, and those having difficulty in essential activities of daily living may require vigilant follow-up.